Cover Image. (1st August 2019) - Sangiovanni, Enrico; Fumagalli, Marco; Pacchetti, Barbara; Piazza, Stefano; Magnavacca, Andrea; Khalilpour, Saba; Melzi, Gloria; Martinelli, Giulia; Dell'Agli, Mario
Abstract : The cover image is based on the Research Article Cannabis sativa L. extract and cannabidiol inhibit in vitro mediators of skin inflammation and wound injury by Enrico Sangiovanni et al., https://doi.org/10.1002/ptr.6400 . Cover design: Linnea (Art Direction & Graphic Project Elita Studio+Bottega).